2020
DOI: 10.21511/ppm.18(4).2020.04
|View full text |Cite
|
Sign up to set email alerts
|

The economic and social drivers of renewable energy development in OECD countries

Abstract: There are continuous research and practical interest to combine different renewable sources within one Smart Grid network. The paper aims to estimate the influence of key economic and social drivers of renewable energy and Smart Grid promotion in OECD member countries. The random effect of the generalized least squares method was used to estimate the empirical model based on the World Bank, OECD, Heritage Foundation, and World Energy Council datasets for a panel of 36 OECD counties. For the empirical estimatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…Conversely, constructive shocks of RE consumption show a negative correlation with CO 2 emissions Rehman et al ( 2021b ) Pakistan 1985–2017 ARDL approach The results show that trade and RE are constructively linked to GDP growth in the long run Isik et al ( 2021a ) USA, Canada, and Mexico 1961–2016 Panel unit root test The findings show that there is convergence of ecological footprint in the second regime, which represents %48.08 of the sample, and difference in the first Isik et al ( 2021b ) 8 OECD Countries 1962–2015 Regression Empirical findings indicate that the undecomposed model with undecomposed per capita GDP series supports the EKC hypothesis for 4 out of 8 countries Dogru et al ( 2020 ) OECD Countries 1995–2014 Panel data analysis The findings showed that tourism development has negative and significant effects on CO 2 emissions in Canada, Czechia, and Turkey, while tourism development has positive and significant effects on CO 2 emissions in Italy, Luxembourg, and the Slovak Republic Egli, ( 2020 ) Germany, Italy, and UK 2009–2017 Network analysis Risks of investment in RE technologies are constraint, policy, price, resource, and technology. It is revealed that risk premiums and investment risk for solar photovoltaics and onshore wind technologies have decreased in all three countries Melnyk et al ( 2020 ) 36 OECD Countries 2001–2015 Panel data analysis The results show that an increase of US$10,000 in GDP in national economies led to an average decrease of 3.9% in renewable electricity generation over the period 2001–2015 Isik et al (2019a) 10 US states 1980–2015 Panel estimation method …”
Section: Appendixmentioning
confidence: 99%
“…Conversely, constructive shocks of RE consumption show a negative correlation with CO 2 emissions Rehman et al ( 2021b ) Pakistan 1985–2017 ARDL approach The results show that trade and RE are constructively linked to GDP growth in the long run Isik et al ( 2021a ) USA, Canada, and Mexico 1961–2016 Panel unit root test The findings show that there is convergence of ecological footprint in the second regime, which represents %48.08 of the sample, and difference in the first Isik et al ( 2021b ) 8 OECD Countries 1962–2015 Regression Empirical findings indicate that the undecomposed model with undecomposed per capita GDP series supports the EKC hypothesis for 4 out of 8 countries Dogru et al ( 2020 ) OECD Countries 1995–2014 Panel data analysis The findings showed that tourism development has negative and significant effects on CO 2 emissions in Canada, Czechia, and Turkey, while tourism development has positive and significant effects on CO 2 emissions in Italy, Luxembourg, and the Slovak Republic Egli, ( 2020 ) Germany, Italy, and UK 2009–2017 Network analysis Risks of investment in RE technologies are constraint, policy, price, resource, and technology. It is revealed that risk premiums and investment risk for solar photovoltaics and onshore wind technologies have decreased in all three countries Melnyk et al ( 2020 ) 36 OECD Countries 2001–2015 Panel data analysis The results show that an increase of US$10,000 in GDP in national economies led to an average decrease of 3.9% in renewable electricity generation over the period 2001–2015 Isik et al (2019a) 10 US states 1980–2015 Panel estimation method …”
Section: Appendixmentioning
confidence: 99%
“…However, analysis of the energy factor remains unclear, mainly due to the lack of distinction in the forms of energy. Melnyk et al (2020) concluded that "the development of the service economy contributes to the dematerialization of economic systems, and stimulates energy use reduction and energy efficiency growth through the renewable energy development." Nycz-Wróbel (2021) and Yevdokimov et al (2018) stated that the goal of shifting to alternative energy sources (e.g., liquid gas, natural gas, or renewable energy sources -wind energy, photovoltaic energy, solar energy, biomass, geothermal energy (utility vehicles), hydroelectric power (paper)) is to reduce emissions of pollutants into the air.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The author concludes by arguing that economic growth policies should encourage renewable energy to facilitate economic growth and increase energy independence at the country level. [8] consider the relationship between renewable energy production and gross domestic product in 36 OECD countries over the period 2001-2015. The authors verify the existence of a negative relationship between GDP growth and an increase in the production of renewable energy.…”
Section: Literature Reviewmentioning
confidence: 99%